Time To Shine Bright : History of a Pavilion : Algerians Artists in l'enice. - Zoubir, Hellal Mahmoud; Bird, Fadela; Dorbani-Bouabdellah, Malika; Mercier, Jeanne; Orif, Mustapha; Saou-Dufrêne, Bernadette Nadia; Toumi, Samir ([S.l.] : Éditions Helium, 2019)
Azdaou, Rachida ; Krinah, Mourad ; Zoubir, Amina ; Bounoua, Hamza ; Tabti, Oussama
Time To Shine Bright, Venice Biennale, Venice, May 11th to November 24th 2019
boek